The diagnosis of uterine cervical polyps in a low resource setting: the positive predictive value of clinical judgment – a series of 192 cases at the Yaoundé Gynaeco-Obstetric and Paediatric Hospital, Cameroon. (April 2013) - Foumane, Pascal; Sando, Zacharie; Dohbit, Julius Sama; Bilo'o, Lydienne Lesly; Mboudou, Emile Telesphore; Oyono, Jean Louis Essame
As far as we know, the accuracy of clinical judgment in diagnosing uterine cervical polyps has not been assessed in sub-Saharan Africa. Our objective was to discover the positive predictive value (PPV) of clinical judgment in the diagnosis of cervical polyps. This is a retrospective descriptive study of 192 patients, carried out by the Departments of Pathology and Gynaecology of the Yaoundé Gynaeco-Obstetric and Paediatric Hospital, Cameroon. The diagnosis of cervical polyp was confirmed by histopathology examination in 169 patients, giving a PPV rate of 88.0%. The PPV of clinical judgment in the diagnosis of cervical polyps is acceptable in our setting but the frequency of premalignant and malignant lesions encountered is too high (10.4%), even in the presence of a confirmed cervical polyp (8.9%). Even in areas where there are limited resources, we recommend a systematic histopathology examination of any clinically suspected cervical polyp.